Georgia O'Keeffe in Texas : a guide - Carlson, Paul Howard; Becker, John T. (John Taylor) (Buffalo Gap, Tex. : State House Press, 2012)
"Georgia O'Keeffe, a superbly gifted American artist usually associated with New Mexico, spent nearly four years in Texas, most of them in the Panhandle. She taught art in the public schools of Amarillo for two years, 1912-1914, and headed the art department at West Texas Normal College (now West Texas A & M University) in Canyon from the fall of 1916 to early 1918. She then went for a few months to Waring, Texas, northwest of San Antonio. There are scores of books on Georgia O'Keeffe. The books are of various lengths, covering her life, art, and influence on other artists; her time spent in New Mexico; and her relationship with and marriage to Alfred Stieglitz. By comparison, however, there is little on O'Keeffe's years in Texas. Georgia O'Keeffe in Texas: A Guide is different from previous O'Keeffe studies, as it provides a short biography of O'Keeffe on the people and events that influenced her Texas years. The authors are neither artists nor professional art critics, but are historians of the American West who have an interest in Georgia O'Keeffe. They believe her years in Texas, especially the Texas Panhandle, were significant for her subsequent development as a thoroughly modern American artist. This book is designed to work as a guide to O'Keeffe's life and work in Texas, and reveals an even more fascinating figure in the process. Front Cover Art Credit: Panhandle-Plains Historical Museum, Canyon, Texas"--
"The book will provide a short biography of O'Keeffe and six brief "sidebars" on people or events that influenced her Texas years. The book will have several photos of Amarillo, Canyon, the schools in which she taught, and Palo Duro Canyon, plus appropriate persons connected with her work in Texas. There will be maps of Texas, the Panhandle, Amarillo, and Canyon plus one that will show the geographic relationship between the Texas Panhandle and O'Keeffe's New Mexico country: Taos, Ghost Ranch, Abiquiu, Rancho de los Burros, and Pedernal. It will describe some of the extant paintings O'Keeffe completed in Texas, note several of her series of paintings, and discuss the art themes and topics she first developed in the Panhandle and refined while working in New Mexico"--
Chronology -- Biography -- Amarillo, Canyon, and the Texas Panhandle -- Modernism and art -- Dow Method -- Georgio O'Keeffe and Arthur Stieglitz -- Ted Reid -- Leah Harris -- Paul Strand -- Canyon Suite -- The Influence of the Texas Panhandle on Georgia O'Keeffe / by John F. Matthews -- Descriptions of O'Keeffe's Texas Art -- Texas Museums Holding Art of Georgia O'Keeffe.
Includes bibliographical references (pages 121-127) and index.
Keywords: O'Keeffe, Georgia, -- 1887-1986.; O'Keeffe, Georgia, -- 1887-1986 -- Friends and associates; O'Keeffe, Georgia, -- 1887-1986; Artists -- United States -- Biography; Texas -- Biography; ART -- Individual Artists -- General; HISTORY -- United States -- State & Local -- Southwest (AZ, NM, OK, TX); BIOGRAPHY & AUTOBIOGRAPHY -- Artists, Architects, Photographers; BIOGRAPHY & AUTOBIOGRAPHY -- Women; Artists; Friendship; Texas; United States; Biography